A study on the standardization of perioperative nursing activities based on the Nursing Intervention Classification (NIC) - Kim, Jieun (International Journal of Engineering and Technology, 2019)
This study was conducted to propose measures for standardizing perioperative nursing activities in Korea based on NIC. Perioperative nursing activities were reviewed by an expert group and compiled into a list. They were then classified based on NIC interventions, and a validity questionnaire was developed. The questionnaire was distributed to 39 clinical nurses who had at least 10 years of experience in operating rooms to investigate the classification validity. The general characteristics of research subjects were expressed in real numbers and percentages. The validity of NIC interventions and perioperative nursing activity factors was assessed using the validity of â€œclarity,â€ â€œinclusiveness,â€ â€œmutual exclusiveness,â€ â€œhomogeneity,â€ and the mean validity score. The reliability of the questionnaire was assessed using Cronbachâ€™s Alpha, and the construct validity was assessed using exploratory factor analysis. Standardization measures were presented for perioperative nursing activities and classified into 5 domains and 14 classes. The proposed standardization measures for perioperative nursing activities, which take into account the circumstances in Korea, are expected to be useful in digitizing nursing records and serving as a basis for calculating nursing costs.Â Â